Role of Flavonoinds From Nigella sativum seeds in Decreasing the Effect of Hydrogen Peroxide on ECG in Adult Male Rabbits - Al-Okaily, Barra Najim (The Iraqi Journal of Veterinary Medicine, 2009)
This experiment was carried out to evaluate the role of flavonoinds of Nigella sativum seeds to reduce theeffect of hydrogen peroxide on electrocardiography in rabbits. Eighteen adult male rabbits were divided intothree equal groups (6\group) and were treated for six weeks as follows: first group (control), which were givenordinary tap water, second treated group (T1), animals in this group given 0.5%H2O2 in drinking water andthird treated group (T2) was handled as in T1 plus oral intubation of flavonoinds (27.5mg\Kg B.W).Electrocardiography was recordings from rabbits after 3 and 6 weeks of treatment. The results conducted thatH2O2 treated group (T1) showed significant increased in P-R interval, R-voltage and significant decreased in Twavevoltage and heart beats. While treatment of animals with flavonoinds of Nigella sativum seeds causedsignificant decrease in P-R interval and R-voltage with an increase in T-wave voltage and heart beats, direct toward their control levels. It was concluded that the flavonoinds of Nigella sativum can ameliorate the deleteriouseffects of hydrogen peroxide on electrocardiography .More studies are needed to convince these findings.